Associations between ultrafine and fine particles and mortality in five central European cities - Results from the UFIREG study - Lanzinger, Stefanie; Schneider, Alexandra; Breitner, Susanne; Stafoggia, Massimo; Erzen, Ivan; Dostál, Miroslav; Pastorkova, Anna; Bastian, Susanne; Cyrys, Josef; Zscheppang, Anja; Kolodnitska, Tetiana; Peters, Annette (Environment international, 2016)
BACKGROUND: Evidence on health effects of ultrafine particles (UFP) is still limited as they are usually not monitored routinely. The few epidemiological studies on UFP and (cause-specific) mortality so far have reported inconsistent results. OBJECTIVES: The main objective of the UFIREG project was to investigate the short-term associations between UFP and fine particulate matter (PM)<2.5μm (PM2.5) and daily (cause-specific) mortality in five European Cities. We also examined the effects of PM<10μm (PM10) and coarse particles (PM2.5-10). METHODS: UFP (20-100nm), PM and meteorological data were measured in Dresden and Augsburg (Germany), Prague (Czech Republic), Ljubljana (Slovenia) and Chernivtsi (Ukraine). Daily counts of natural and cardio-respiratory mortality were collected for all five cities. Depending on data availability, the following study periods were chosen: Augsburg and Dresden 2011-2012, Ljubljana and Prague 2012-2013, Chernivtsi 2013-March 2014. The associations between air pollutants and health outcomes were assessed using confounder-adjusted Poisson regression models examining single (lag 0-lag 5) and cumulative lags (lag 0-1, lag 2-5, and lag 0-5). City-specific estimates were pooled using meta-analyses methods. RESULTS: Results indicated a delayed and prolonged association between UFP and respiratory mortality (9.9% [95%-confidence interval: -6.3%; 28.8%] increase in association with a 6-day average increase of 2750particles/cm(3) (average interquartile range across all cities)). Cardiovascular mortality increased by 3.0% [-2.7%; 9.1%] and 4.1% [0.4%; 8.0%] in association with a 12.4μg/m(3) and 4.7μg/m(3) increase in the PM2.5- and PM2.5-10-averages of lag 2-5. CONCLUSIONS: We observed positive but not statistically significant associations between prolonged exposures to UFP and respiratory mortality, which were independent of particle mass exposures. Further multi-centre studies are needed investigating several years to produce more precise estimates on health effects of UFP.
Keywords: kardiovaskulární nemoci; látky znečišťující vzduch; dítě; pevné částice; Aged; Adolescent; velikost částic; Air Pollutants; Cause of Death; lidé středního věku; senioři; předškolní dítě; velkoměsta; Cities; lidé; Adult; Middle Aged; Respiration Disorders; dospělí; Europe; Models, Theoretical; kojenec; Female; znečištění ovzduší; poruchy dýchání; Male; Particulate Matter; ženské pohlaví; mladý dospělý; Child; Humans; mužské pohlaví; Young Adult; příčina smrti; Particle Size; Infant; Air Pollution; Child, Preschool; Evropa; teoretické modely; Cardiovascular Diseases; mladiství